Geochemical features of soils in an undulating glaciolacustrine sandy plain in the middle taiga subzone of Karelia - G. V. Akhmetova (Бюллетень Почвенного института им. В.В. Докучаева, 2020)
The geochemically conjugate series of soils (Albic Podzol – Albic Podzol Gleyc – Hystosol) formed on an undulating glaciolacustrine plain in the middle taiga of Karelia was investigated. Surveys for redox conditions showed them to vary from oxidizing in automorphic soils to reducing in soils occupying accumulation-favoring locations. The geochemical coefficients descriptive of the features of accumulation and directions of migration in the studied soils were calculated and analyzed. The distribution of silicic acid and a majority of sesquioxides inside the profile of the studied soils is typical of podzols. The podzolic horizons of the soils occupying interstitial positions have a faster outmigration of elements than in automorphic soils, while their Al-Fe-humic horizons accumulate aluminum, iron, titanium and phosphorus. All the soils are deficient in a majority of microelements as compared to their background levels; very low concentrations were determined for nickel, cobalt and manganese. The content of copper and sometimes zinc is at the background level. The distribution of the studied elements across the soil profile follows the accumulation-eluviation-illuviation pattern, but the scope of variation in the migration of elements varies among topographic positions. In well-drained locations microelements are quite monotonously distributed through the lower part of the soil profile, while soils in transitional landscapes have a higher differentiation of microelements. The differentiation of the catena through lateral migration is of the transient eluviation type, i.e. soils in lower-lying positions are poorer in the studied elements than soils in automorphic positions. This pattern is due to the natural characteristics of the area: low surface slope, homogeneous sandy parent material, low humus content in soil.